Implementasi Sistem Kasir Berbasis Web untuk Modernisasi Pelayanan di Warkop A Place Gunung Sindur Bogor - Yopi Sunan Nugraha; Azka Zulfarazil; Annisa Ananda Putri; Nurhalimah Nurhalimah (ARDHI : Jurnal Pengabdian Dalam Negri, 2026)
Warkop A Place is a mini coffee shop offering a variety of coffee blends and light snacks to its customers. In its day-to-day operations, this coffee shop still relies heavily on conventional paper-based methods to record transactions. This manual approach to handling customer orders, payments, and financial logs frequently leads to clerical errors, prolonged queues during peak hours, and disorganized sales monitoring. To overcome these operational vulnerabilities, this study aims to design and build a web-based cashier system integrated with an automatic label printing feature to elevate service efficiency and accuracy at Warkop A Place. The system development workflow follows the Prototyping model, driving an active feedback loop through client requirement gathering, quick design modeling, prototype construction, user evaluations, and final deployment. On the technical spectrum, the software is engineered using PHP and MySQL database, alongside HTML, CSS, and JavaScript for an optimized frontend user interface. The fully developed POS application delivers essential components, including menu catalog controls, a transactional node, staff account modules, receipt generation, and instantaneous sticker label printing post-payment validation. Post-implementation results demonstrate that the web application drastically accelerates transaction speeds, eliminates order mix-ups at the barista counter, and generates highly structured financial summaries. Ultimately, this web-based cashier system successfully modernizes and streamlines operational workflows at Warkop A Place.